The role of epigenetic factors in the pathogenesis of dysmetabolic nephropathy with calcium oxalate crystalluria in children - N.R. Aib; O.Z. Hnateyko; N.S. Lukyanenko; A.B. Volosyanko (Сучасна педіатрія: Україна)
The prevalence of dysmetabolic nephropathies in children is increasing from year to year, representing a significant problem in the overall structure of kidney diseases in pediatric age. Despite numerous studies dedicated to the issue of dysmetabolic nephropathies in children, the role of epigenetic factors in the pathogenesis of dysmetabolic nephropathy with calcium oxalate crystalluria remains insufficiently explored.